ANALISIS EFESIENSI PENGGUNAAN FAKTOR – FAKTOR PRODUKSI PADA INDUSTRI KERAJINAN ROTAN DI KECAMATAN RUMBAI KOTA PEKANBARU - Maya Izayara; Gusnardi Gusnardi; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Rattan handicraft production continues to increase along with the increasing number of rattan handicraft industry entrepreneurs in Rumbai District, Pekanbaru City. However, the problem in the production of the rattan handicraft industry in Rumbai District, Pekanbaru City is the lack of attention of craftsmen to the quality of the goods produced and price competition that does not compete with other non-handicraft products. This study aims to analyze the technical, price and economic efficiency in the use of capital production factors, raw materials and labor in the rattan handicraft industry in Rumbai District, Pekanbaru City. The object of this research is the rattan industry entrepreneurs in Rumbai District, Pekanbaru City, amounting to 23 rattan handicraft industry entrepreneurs based on data obtained from the Pekanbaru City Industry and Trade Office in 2018. Data analysis uses descriptive analysis and data analysis uses Stochastic Production Frontier- Technical Efficiency ( SPF-TE). The results of this study indicate that the efficiency of rattan production in Rumbai District based on the stochastic frontier is considered efficient because the average efficiency value is close to 1. Furthermore, the efficiency of rattan prices is considered inefficient because the average value of efficiency is small from 1.Finally, the economic efficiency of rattan in Based on the stochastic frontier, Rumbai District is considered efficient because the average efficiency value is close to 1.Keyword : Efficiency, Production Factors, Rattan Crafts